Assessment of Soil Salinity on Grand Bahama Post-Hurricane Dorian - Stubbs, Danica; Adderley, Aaliyah; Bowen-O’Connor, Clare; Watson, Carlton; Gustave, Williamson (International Journal of Bahamian Studies, 2023)
Saltwater intrusion into land is becoming more of a problem as sea levels rise across the globe. The Bahamas is highly susceptible to extreme weather events and climate change because the islands are low-lying and located in the Atlantic hurricane belt. Hurricane Dorian (2019) had a devastating impact on Grand Bahama Island: producing heavy rains of up to 30-40 cm and storm surges of about 8 m. The objective of this study was to analyse the soil salinity status in Wellfields 1 and 6 on the island of Grand Bahama to determine if the salinity had decreased in the three years following Hurricane Dorian. As expected, the study found that by 2022, soil salinity in the wellfields had decreased compared to levels recorded in the year after Hurricane Dorian. Soil analysis completed in October 2022 illustrated that soil salinity averaged 475.5 mg/kg for both Wellfield 1 and Wellfield 6 on the island of Grand Bahama.